2022
DOI: 10.54393/pbmj.v5i6.558
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Modified ELDOA Technique in Patients with Cervical Radiculopathy

Abstract: ELDOA is a revolutionary technique for improvement of health and longevity of the spine which is introduced by French osteopath; Guy Voyer. The primary goal of ELDOA is to apply focused internal tension and load to decrease pressure on the discs of spine, increase blood flow and to reduce pain at cervical spine. There is little high-quality evidence on best no operative therapy for cervical radiculopathy. Objective: To determine the effects of Modified ELDOA technique in patients with cervical radiculopathy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Treatment for cervical radiculopathy involves modified ELDOA and postures. The difference between the efficacy of ELDOA and modified ELDOA is not statistically significant 14 .…”
Section: Discussionmentioning
confidence: 74%
“…Treatment for cervical radiculopathy involves modified ELDOA and postures. The difference between the efficacy of ELDOA and modified ELDOA is not statistically significant 14 .…”
Section: Discussionmentioning
confidence: 74%
“…Another study conducted on the effects of modified ELDOA and ELDOA on cervical radiculopathy reported that both interventions were effective in improving posture and disabilities; however, no significant difference was found. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on the effects of modified ELDOA and ELDOA on cervical radiculopathy reported that both interventions were effective in improving posture and disabilities; however, no significant difference was found. [23] Brück et al [36] conducted a clinical trial in 2021 to compare the effects of fascial therapy and manual therapy among patients of chronic neck pain. In the past literature fascia targeted therapy grabs the attention of physiotherapists as it has beneficial effects on chronic neck pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations